Reversible Superwetting Transition Between Superhydrophilicity and Superhydrophobicity on a Copper Sheet, and Its Corrosion Performance - Li, Hong; Chen, Tiange; Lu, Yanfeng; Fu, Xinyu; Chu, Xingwen; Liu, Qinzhuang; Zhang, Jinfeng (Frontiers in Materials, 2021)
Dense copper oxide nanoribbons arrays are prepared on copper sheet using low temperature hydrothermal method. The wettability of the surface modified by stearic acid is superhydrophobic and water contact angle is 153.6°. It is demonstrated that the reversible transition from superhydrophilicity to superhydrophobicity are successfully achieved by heat treatment and re-modification, and the whole process can be accomplished in 170 s. Potentiodynamic polarization curves and Nyquist curves show that this superhydrophobic surfaces have good corrosion resistance and superior durability.